2004
DOI: 10.1538/expanim.53.453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Six-and Ten-Day-Old Chick Embryo Amniotic Fluid on Development of Two-Cell Mouse Embryos

Abstract: Abstract:The purpose of this study was to investigate the effect of six-and ten-day-old chick embryo amniotic fluid (CEAF) on the development of two-cell mouse embryos. Sixand ten-day-old CEAF (6-AF, 10-AF) were aspirated separately from the amniotic cavity and two experiments were performed. In the first experiment, two-cell mouse embryos were cultured in different supplements of heat-inactivated 6-AF, pure heat-inactivated 6-AF and pure active 6-AF. The second experiment was also carried out in the same mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The fractions of peak 1-10 were separated according to the peak time of HPLC. Briefly, Acetonitrile (ACN) and ddH 2 O were used as mobile phases and separated the different fractions by C 18 reverse phase separation column. The first thing is to equilibrate reversed phase column until the UV absorption curve at 280 nm was stable and returned to the baseline with mobile phase 3% ACN.…”
Section: Preparation and Separation Of P8mentioning
confidence: 99%
See 1 more Smart Citation
“…The fractions of peak 1-10 were separated according to the peak time of HPLC. Briefly, Acetonitrile (ACN) and ddH 2 O were used as mobile phases and separated the different fractions by C 18 reverse phase separation column. The first thing is to equilibrate reversed phase column until the UV absorption curve at 280 nm was stable and returned to the baseline with mobile phase 3% ACN.…”
Section: Preparation and Separation Of P8mentioning
confidence: 99%
“…AF maintains acid/base balance and contains nutrients, growth factors, and cytokines ( 16 , 17 ). As a supplement of natural medium, 6- and 10- day-old chick embryo AF can sustain the development of two-cell mouse embryos ( 18 ). Moreover, it has been shown that chick embryo AF can promote peripheral nerve regeneration in rats ( 19 ) and rat AF can prevent intraperitoneal adhesion formation in surgical operation ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…While in early embryonic development, AF mainly comes from the egg per se which also serves the function of delivering nutrition similar to blood (Larsen 1993 ). Chick early amniotic fluid (ceAF) can support the development of two-cell mouse embryos (Esmaili and Rezazadeh Valojerdi 2004 ) and is important for fetal health (Gitlin et al 1972 ; Pitkin and Reynolds 1975 ). Additionally, ceAF can be a source or supplement of cell culture medium (Larsen 1993 ; Wang et al 1997 ).…”
Section: Introductionmentioning
confidence: 99%